(3TQM GdCOhjI GdeaQOI ef cJGH GdbGfhfs - (3CaVd GdOjf YeQ Hf Ydj Hf ZjdGf GdHdNis; (3GdQFjS GHf SjfG , CHh Ydj TQa Gdedc (B: (3GdajdSha GdQFjS,J (B428 (3g` s
(3ChdgG (B:s
(3bGd GdTjN GdEeGe Efi JUaMJ cJGH GdCOhjI GdeaQOI ef cJGH GdbGfhf ai GdWH dCHi Ydi Hf SjfG , ahLOJ ef GdENJdGa hGdJaGhJ hGdJfGbV eG jOd Ydi Cf Ld eG ajg efbhd ef cJH eJbOeI eNJdaI s
(3BNQgG (B:s
(3hCf jhLO Hg eKdg , dcf dceGd XghQg UdM dJScjJ ef jYJeO Cfg eYUhe Yf GdRdd , hCf GdNWC Ydjg eMGd s
(3Vef eLehY , JQJjHgG (B: (3ef U (B399 - (3U(B402s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B124 s
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThGQi edi (B(1538) s
Keywords: (3GdWHs